2014
DOI: 10.1016/j.pbb.2013.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Repeated alcohol extinction sessions in conjunction with MK-801, but not yohimbine or propranolol, reduces subsequent alcohol cue-induced responding in rats

Abstract: Cues associated with alcohol can stimulate subjective states that increase relapse. Alcohol-cue associations may be strengthened by enhancing adrenergic activity with yohimbine or weakened by blocking adrenergic activity with propranolol. Alcohol-cue associations may also be weakened by long cue exposure sessions or strengthened by short cue exposure sessions. A useful treatment approach for alcoholism may combine adrenergic manipulation with cue exposure sessions of a specific duration. The present study soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…In contrast to the original hypothesis, post-reactivation propranolol had no effect on cue-induced reinstatement, indicative of no effect on It is not surprising, however, that propranolol failed to block reconsolidation as measured by cue-induced reinstatement. Previous research indicates that propranolol is not always effective at interfering with reconsolidation in both rodents Font and Cunningham 2012;Milton et al 2012;Williams and Harding 2014) and humans (Tollenaar et al 2009;Bos et al 2014;Pachas et al 2015;Spring et al 2015;Wood et al 2015), and replications of experiments even within the same laboratory have produced differing results (Kindt et al 2009;Bos et al 2014). Some explanations for these inconsistencies include the ability of propranolol to preferentially affect emotional memories over neutral memories (Schwabe et al 2012a,b), individual differences in participants (Soeter and Kindt 2013), and the mnemonic paradigm under investigation Wei and Li 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the original hypothesis, post-reactivation propranolol had no effect on cue-induced reinstatement, indicative of no effect on It is not surprising, however, that propranolol failed to block reconsolidation as measured by cue-induced reinstatement. Previous research indicates that propranolol is not always effective at interfering with reconsolidation in both rodents Font and Cunningham 2012;Milton et al 2012;Williams and Harding 2014) and humans (Tollenaar et al 2009;Bos et al 2014;Pachas et al 2015;Spring et al 2015;Wood et al 2015), and replications of experiments even within the same laboratory have produced differing results (Kindt et al 2009;Bos et al 2014). Some explanations for these inconsistencies include the ability of propranolol to preferentially affect emotional memories over neutral memories (Schwabe et al 2012a,b), individual differences in participants (Soeter and Kindt 2013), and the mnemonic paradigm under investigation Wei and Li 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While post-reactivation propranolol has been shown to reduce conditioned reinforcement in a rodent model of cocaine self-administration (Milton et al 2008), preliminary data from the same laboratory indicate that under the same conditions post-reactivation propranolol may not block cue-induced reinstatement Everitt 2009, 2010), which is supported by the present results. Furthermore, while alcohol conditioned reinforcement is blocked by post-reactivation propranolol similarly to cocaine (Milton et al 2008;Schramm et al 2015), alcohol conditioned motivation and approach are not Milton et al 2012), and the effect of propranolol on cue-induced reinstatement to alcohol-seeking is unclear (Wouda et al 2010;Williams and Harding 2014). Thus, it is likely that propranolol selectively or preferentially modifies the reconsolidation of conditioned reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, rodents are trained to lever press or nose poke for rewards, such as food, intravenous drug infusion, or intracranial stimulation (eg, of the lateral hypothalamus). Experiments have revealed that systemic propranolol injections administered after memory retrieval disrupt context-or cue-driven sucrose seeking (Diergaarde et al, 2006;Milton et al, 2008b), cocaine seeking (Milton et al, 2008b), and ethanol seeking (Wouda et al, 2010) within the SA paradigm (but see Milton and Everitt, 2010;Williams and Harding, 2014). However, these convincing experiments have been overshadowed by studies revealing no effect of propranolol when administered before memory retrieval (Lee and Everitt, 2008;Milton and Everitt, 2010).…”
Section: Rodent Sa Studiesmentioning
confidence: 99%
“…Synaptic plasticity is a critical mechanism for reconsolidation (Clem and Huganir, 2010). Moreover, NMDA receptor Impaired Sucrose (CR) Milton et al (2008b) Impaired Cocaine (CR) Milton et al (2008b) No effect Cocaine (reinstatement) Milton and Everitt (2010) Impaired EtOH (extinction) Wouda et al (2010) No effect EtOH (extinction) Williams and Harding (2014) Before No effect Sucrose (PCA) Lee and Everitt (2008) No effect Sucrose (PIT) Lee and Everitt (2008) No effect EtOH (PCA) Milton et al (2012) No effect EtOH (PIT) Milton et al (2012) Abbreviations: CR, conditioned reinforcement; PCA, Pavlovian conditioned approach; PIT, Pavlovian-to-instrumental transfer. Summary of findings for research examining the effectiveness of propranolol for reconsolidation blockade within the SA paradigm.…”
Section: Cellular Mechanismsmentioning
confidence: 99%
“…The acquisition of these appetitive conditioned responses depends on the ventral tegmental area, striatum, amygdala, and, for contextual information, the hippocampus (Everitt 2014; Everitt and Robbins 2005; Robbins et al 2008). Memory reactivation combined with noradrenergic antagonists has been reported to reduce self-administration behaviour of cocaine and sucrose but may be more limited for alcohol (Diergaarde et al 2006; Milton et al 2008; Williams and Harding 2014; Wouda et al 2010). In addition, studies have reported an attenuation of CPP by beta-blockers following memory reactivation (Bernardi et al 2006, 2009; Fricks-Gleason and Marshall 2008; Robinson and Franklin 2007), although effects have not always been equally strong in that memory has been found to recover over time (Fricks-Gleason and Marshall 2008; Robinson and Franklin 2007), and more remote memories may be more resistant to modification (Robinson and Franklin 2010; Robinson et al 2011).…”
Section: Biological Interventions Targeting Reconsolidationmentioning
confidence: 99%